PENGGUNAAN METODE NN UNTUK MENGUKUR PENGARUH WEB PROMOSI DAN FAKTOR HARGA TERHADAP PENJUALAN KAIN TENUN OLEH PENGRAJIN DI PRINGGASELA LOMBOK TIMUR - Baiq Andriska Candra Permana; Indra Gunawan; Ramli Ahmad (Infotek: Jurnal Informatika dan Teknologi, 2019)
Selling woven fabric products using an online system will certainly lead to lower production costs and lower selling prices. Online selling requires a concept and a mature mind to find out important things that can attract consumers to visit the website and make purchases. With this research the seller will get an overview of the things that can attract consumers to purchase woven fabric based on several variables studied, like the promotion website and the selling price of woven fabric. From this variables seller can find out which variable has the most influence on the buyer's decision to purchase Lombok woven fabric, in this case the researcher conducted a study on this matter by analyzing using the Neural Network (NN) model. Base on the analysis that has been done, a result is obtained, where the variables that have the greatest influence on the purchase decision of woven fabric are prices and websites with an accuracy level of PRED (.25) of 95%.DOI : 10.29408/jit.v2i1.975